PERBANDINGAN KENAKALAN REMAJA ANTARA REMAJA PEDESAAN DAN REMAJA PERKOTAAN (STUDI KASUS SMA X DAN SMA Y) - Widya Ramailis, Neri; Wulandari, Dita (SISI LAIN REALITA, 2021)
Adolescence seems to never be separated from the name of delinquency or social deviation. Many factors are the cause of juvenile delinquency. Every teenager has different personalities and lives in different environments, and that causes each teenager to have different causes and forms of delinquency. Like rural youth and urban youth. Between rural teenagers and urban teenagers have very big differences such as the environment, family, education, relationships, and so on. Through quantitative research methods by distributing questionnaires in two schools namely SMA X and SMA Y as representatives of rural youth and urban youth, as well as conducting interviews with BK teachers of both schools, researchers found that SMA X in Maredan village has a record of the delinquency that occurs in 2018 included truancy, courtship, smoking and theft. SMA Y in Pekanbaru City has a record of the forms of delinquency that occurred in 2018, among others, namely truancy, courtship, smoking, immorality, theft, and class fights. While the causes of delinquency that the researchers analyzed using social ties theory showed the results of a dominant to non-dominant indicator arrangement, namely commitment, attachment, belief, and involvement. And SMA Y is attachment, commitment, belief, and involvement.